Pharmacological agents targeting drug-tolerant persister cells in cancer - Yu-Chi Chen; Krishne Gowda; Shantu Amin; Todd D. Schell; Arun K. Sharma; Gavin P. Robertson (Elsevier, 2024)
Current cancer therapy can be effective, but the development of drug resistant disease is the usual outcome. These drugs can eliminate most of the tumor burden but often fail to eliminate the rare, "Drug Tolerant Persister" (DTP) cell subpopulations in residual tumors, which can be referred to as "Persister" cells. Therefore, novel therapeutic agents specifically targeting or preventing the development of drug-resistant tumors mediated by the remaining persister cells subpopulations are needed. Since approximately ninety percent of cancer-related deaths occur because of the eventual development of drug resistance, identifying, and dissecting the biology of the persister cells is essential for the creation of drugs to target them. While there remains uncertainty surrounding all the markers identifying DTP cells in the literature, this review summarizes the drugs and therapeutic approaches that are available to target the persister cell subpopulations expressing the cellular markers ATP-binding cassette sub-family B member 5 (ABCB5), CD133, CD271, Lysine-specific histone demethylase 5 (KDM5), and aldehyde dehydrogenase (ALDH). Persister cells expressing these markers were selected as the focus of this review because they have been found on cells surviving following drug treatments that promote recurrent drug resistant cancer and are associated with stem cell-like properties, including self-renewal, differentiation, and resistance to therapy. The limitations and obstacles facing the development of agents targeting these DTP cell subpopulations are detailed, with discussion of potential solutions and current research areas needing further exploration.